1986
DOI: 10.1007/978-3-642-82785-3
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung der spanenden Bearbeitung von Knochen

Abstract: Das Werk ist urheberrechtlich geschOtzt. Die dadurch begrOndeten Rechte, insbesondere die der Obersetzung, des Nachdrucks, der Entnahme von Abbildungen, der Funksendung, der Wiedergabe auf photomechanischem oder ahnlichem Wege und der Speicherung In Datenverarbeitungsanlagen bleiben, auch bei nur auszugsweiser Verwendung, vorbehalten. Die VergOtungsansprOche des § 54, Abs. 2 UrhG werden durch die "Verwertungsgesellschaft Wort", MOnchen, wahrgenommen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…The results showed that no forces over 20 N were to be expected; this was in accordance to previous studies performed on human bone (2,20). In this study, the characteristics of different systems of leg fixation were investigated to determine parameters required for the programming of the navigational tracking system to control the robotic system, depending on the movement of the patient during the milling process, as additional parameters for the control loop of the robotic system.…”
Section: Introductionsupporting
confidence: 78%
“…The results showed that no forces over 20 N were to be expected; this was in accordance to previous studies performed on human bone (2,20). In this study, the characteristics of different systems of leg fixation were investigated to determine parameters required for the programming of the navigational tracking system to control the robotic system, depending on the movement of the patient during the milling process, as additional parameters for the control loop of the robotic system.…”
Section: Introductionsupporting
confidence: 78%
“…Cobb et al claim an accuracy of 0.5 mm for robotic-assisted UKA [9]. Although the proposed workspace dimensions vary, the bone milling forces are quite similar with 25 N [16] for RTHR and 20 N for UKA [3,12].…”
Section: Requirement Analysismentioning
confidence: 91%
“…It is of great importance to avoid heat or mechanical trauma. 6 One effective way to achieve this goal proved to be the force-based speed control implemented in our system. 7 Another important factor, namely the elimination of tall grooves in the cavity floor, is achieved by choosing a small distance between paths.…”
Section: Discussionmentioning
confidence: 99%